Atmospheric bulk deposition of polycyclic aromatic hydrocarbons in Shanghai: Temporal and spatial variation, and global comparison. (November 2017) - Feng, Daolun; Liu, Ying; Gao, Yi; Zhou, Jinxing; Zheng, Lirong; Qiao, Gang; Ma, Liming; Lin, Zhifen; Grathwohl, Peter
Abstract: Atmospheric deposition leads to accumulation of atmospheric polycyclic aromatic hydrocarbons (PAHs) on urban surfaces and topsoils. To capture the inherent variability of atmospheric deposition of PAHs in Shanghai's urban agglomeration, 85 atmospheric bulk deposition samples and 7 surface soil samples were collected from seven sampling locations during 2012–2014. Total fluxes of 17 PAHs were 587-32, 300 ng m −2 day −1, with a geometric mean of 2600 ng m −2 day −1 . The deposition fluxes were categorized as moderate to high on a global scale. Phenanthrene, fluoranthene and pyrene were major contributors. The spatial distribution of deposition fluxes revealed the influence of urbanization/industrialization and the relevance of local emissions. Meteorological conditions and more heating demand in cold season lead to a significant increase of deposition rates. Atmospheric deposition is the principal pathway of PAHs input to topsoils and the annual deposition load in Shanghai amounts to ∼4.5 tons (0.7 kg km −2 ) with a range of 2.5–10 tons (0.4–1.6 kg km −2 ). Graphical abstract: Highlights: PAH deposition flux in Shanghai is categorized as moderate to high on global scale. Their spatial distribution reveals the influence of urbanization/industrialization. Atmospheric deposition is the principal pathway of PAHs input to local topsoils. Other pathways have to be considered for PAH input in urban soil. Abstract : Atmospheric deposition of PAHs revealed the influence of urbanization and industrialization and the relevance of local emissions on Shanghai topsoils.